An analysis of demographic, socio-economic and clinical variables for mental illness and mental illness relapse in south-east nigeria - Onyenekenwa Cyprian Eneh; Chinemelum Amarachukwu Eneh (Scientific Reports, 2024)
Abstract Mental health has come into the front burner of development challenges amid declining socio-economic outcomes, especially in developing countries. Insecurity, conflicts and extremely threatening events, which trigger mental disorders, are common in South-East Nigeria, with many military operations, unknown gunmen attacks and kidnapping leading to the cold-blood assassination and kidnap of dear ones. The study aimed to analyze the demographic, socio-economic and clinical variables for mental illness in South-East Nigeria. Consecutive sampling technique was used to obtain a three-year records of the cases of 380 index and 180 post-index points data of mental illness cases that met the inclusion criteria in a purposively selected public mental health hospital. Data were analyzed using both descriptive and inferential statistics, including frequency count, percentages, chi-square and multinomial logistic regression. Results showed that over a half (55.0%) of the patients were males, and 65.27% had post-primary education. The mean age of patients was 39.87 years. Slightly above half of the cases (55.26%) were single and 56.84% were unemployed. Schizophrenia (68.42%) topped the list of the cases. The rate of relapse was 52.1%, with males being in the majority (61.62%). About 61.62% of those who relapsed were unemployed, 9.60% were into business/trading, and 5.05% were professionals. Those with 5 years and above illness duration had a higher percentage of relapse (52.02%) as well as those with poor drug compliance (66.16%). The mean relapse age was 34.23 years. Educational status, employment status/social class, marital status, and age were socio-economic/clinical factors that associated strongly with relapse at p-value of 0.10. Patients with ≥ 5 and ≤ 3 years duration of illness were 1.17 times on the average more likely to have relapse than those with three or less than 3 years. Onset age for illness predicted 2.479 times more likelihood of relapse. Being employed and having more family support, as against being unskilled/unemployed and not having family support, reduce the likelihood of relapse by 1.110 times on the average. The study recommended policy formulation and implementation for protection against mental illness and mental healthcare provision and access; for tackling unemployment head-on; for improvement of the access to effective treatment of mental illness; and mass education, especially among unemployed, uneducated, singles, and under-35 years of age, to help reduce the high rate of relapse of mental illness in South-East Nigeria.